Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Disiplin Kerja Pada PT Saprotan Utama Nusantara Semarang - Rosmiyati, Sinta; Haziroh, Awanis Linati (Jurnal EMT KITA, 2024)
Discipline is an important need in every business because company goals cannot be achieved without being supported by strong employee work discipline. The level of work discipline possessed by PT Saprotan Utama Nusantara Semarang is still very low. For this reason, this research aims to find out how work environment and work motivation influence work discipline at PT Saprotan Utama Nusantara Semarang. In analyzing the problems that occurred the author used quantitative methods. The respondents in this research were employees of PT Saprotan Utama Nusantara Semarang with a sample of 120 using purposive sampling. The results of this research are that work environment variables and work motivation have a positive and statistically significant effect on work discipline